The most suitable system to grind the whole tooth to use it as graft material - Elio Minetti; Gianna Dipalma; Andrea Palermo; Alessio Danilo Inchingolo; Fabio Viapiano; Angelo Michele Inchingolo; Francesco Inchingolo (Open Exploration Publishing Inc., 2024)
Aim: In regenerative dentistry, the success is influenced by the graft material, which should act as an osteoconductive scaffold. It provides a mineral substrate during resorption and induces the activity of osteoinductive cells capable of producing new bone, platelet growth factors, and cell differentiation factors that guide the differentiation of undifferentiated mesenchymal cells. Given that dentin shares many biochemical characteristics with bone tissue, it has recently attracted considerable interest as a biomaterial for bone repair. The aim of this study is to compare two grinder types to determine the optimal method for producing dentinal particles using a mechanical grinder. Methods: A sample of 40 natural human teeth without restorations, prostheses, or root canal treatments was used and divided into two groups subjected to two different grinder speeds (high-speed and low-speed). Results: The high-speed showed a greater dispersion (53.5% ± 9.89% of the tooth) due to the pulverisation (highly thin granules) of part of the tooth. The low-speed grinder did not pulverize the dentin and the percentage of tooth loss is 9.16% ± 2.34%. Conclusions: The low-speed grinder allows to save a major part of the tooth and has a maximum quantity of graft material but requires more time. Further studies must be promoted to optimise the grinding procedures.